Towards an Ethics of Unity: An Ecological Approach to Overcoming Dispossession in Academic Libraries - Burgess, John (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2021)
Crisis narratives are stories meant to persuade that one exists in a state of emergency. Under extractive capitalism, crisis narratives frame the scope of ethical behaviour in response to crisis. Once set, these crisis ethics promote conformity in labour practices to avoid catastrophe. Surrendering the means to self-define priorities, values, and identity of the academic library profession creates a more pliable work force. This essay uses critical and philosophical methods to apply lessons learned from landscapes ruined by extractive capitalism to professional library practice fractured by alienation, diremption, and dispossession. A critique of the exploitation of ethics of fear and hope is offered, along with a method for identifying these as they appear in crisis narratives. The essay concludes with a recommendation to pursue an ethics of unity, predicated on promoting flourishing through professional mutualism, dedication to direct action, and a focus on sustainability.